Evaluation of Amino Acid Composition as a Geochronometer in Buried Soils on Mount Kenya, East Africa - Mahaney, William; Boyer, Michael; Rutter, Nathaniel (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTA sequence of surface and buried paleosols from the slopes of Mount Kenya, East Africa, has been identified and dated by radiocarbon and amino acid dating techniques in order to elucidate the Quaternary history of the area. Buried paleosols vary in radiocarbon age from 900 to > 40,000 yrs BP. They have developed in glacial and periglacial deposits of variable texture, consisting of a high percentage of clasts of phonolite, basalt and syenite. All but two paleosols are located in the Afroalpine zone (above 3200 m). D/L ratios of amino acids in Ab horizons were determined in order to establish their reliability for relative age dating. Alanine, aspartic acid, glutamic acid, leucine, valine, and phenylalanine were routinely analyzed. Aspartic acid, as in other cases, proved reliable yielding remarkably consistent results, with higher ratios corresponding to increasing age. Other acids analyzed showed distinct trends, although not as convincing as aspartic acid. In most cases, the aspartic acid ratio/ age relationships were supported by radiocarbon dates. D/L ratios of aspartic acid varied from approximately 0.07 for modern samples, to approximately 0.45 in samples > 40,000 years old.